Presence of antibodies against Rotavirus in semi-technical pig farms in Cundinamarca, Colombia (2020)
The aim of this study was to determine the presence of antibodies against rotavirus in pig sera obtained from semi-technical farms in Cundinamarca, Colombia. For this, 170 samples from various age groups were processed, using the Porcine Ingezim Rotavirus (Ingenasa®) diagnostic ELISA kit. The presence of antibodies against Rotavirus was detected in 78.82% of the samples. It is concluded that the animals may have been in contact with the virus at some point in their production cycle, which suggests the need for improvements in the control and prevention of infection.